Pengembangan Kompetensi Civic Enterpreneur Melalui Pembelajaran Keterlibatan Melalui Pendidikan Kewargnegaraan:Menjawab Tantangan dan Peluang dalam Membentuk Warga Negara Global di Era Digital - Ali, Yusuf Faisal; Trihastuti, Meiwatizal; Hidayah, Yayuk (Prodi PPKn FKIP Universitas Pamulang, 2025)
In the rapidly evolving digital era, civic education plays a crucial role in shaping individuals who are active and responsive to global social, political, and economic changes. One relevant concept to be applied is civic entrepreneurship, which combines social entrepreneurship with civic responsibility to create positive change. However, the main challenge in civic education is how to develop civic entrepreneur competencies that are relevant to global dynamics and the increasing use of digital technologies. This study aims to explore how civic entrepreneur competencies can be developed through engagement-based learning in civic education, addressing the challenges and opportunities in the digital era. Using a literature review methodology, this research analyzes various academic sources and theories related to the development of civic entrepreneur competencies, civic education, and their application in a digital context. The findings indicate that engagement-based learning, which involves collaboration, problem-solving, and social entrepreneurship, can foster civic entrepreneur competencies. Moreover, the digital era offers new opportunities to expand civic participation through digital platforms, although it also presents challenges in maintaining the quality of engagement. In conclusion, the development of civic entrepreneur competencies through civic education in the digital era can strengthen social and political participation. Therefore, it is recommended that civic education integrate the concept of civic entrepreneurship with engagement-based learning methods that are more relevant to the needs and challenges of the global digital era.